2012
DOI: 10.1109/tgrs.2011.2180728
|View full text |Cite
|
Sign up to set email alerts
|

The TropiSAR Airborne Campaign in French Guiana: Objectives, Description, and Observed Temporal Behavior of the Backscatter Signal

Abstract: The TropiSAR campaign has been conducted in August 2009 in French Guiana with the ONERA airborne radar system SETHI. The main objective of this campaign was to collect data to support the Phase A of the 7th Earth Explorer candidate mission, BIOMASS. Several specific questions needed to be addressed to consolidate the mission concept following the Phase 0 studies, and the data collection strategy was constructed accordingly. More specifically, a tropical forest data set was required in order to provide test dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…The TropiSAR campaign was conducted in French Guiana in the summer 2009 [1] in the framework of the Phase A studies pertaining to the BIOMASS mission, one of the three for Earth Explorer candidates with the SETHI radar operated by ONERA. In this paper we explore the estimation precision of different forest and ground parameters from single baseline PolInSAR data in this tropical context.…”
Section: Introductionmentioning
confidence: 99%
“…The TropiSAR campaign was conducted in French Guiana in the summer 2009 [1] in the framework of the Phase A studies pertaining to the BIOMASS mission, one of the three for Earth Explorer candidates with the SETHI radar operated by ONERA. In this paper we explore the estimation precision of different forest and ground parameters from single baseline PolInSAR data in this tropical context.…”
Section: Introductionmentioning
confidence: 99%
“…The baselines have been spaced vertically with a spacing about 15 m (50ft ). Since the tomographic flight lines are in a vertical plane rather than in a horizontal plane, the phase to height factor has a small variation across the scene swath [8]. The vertical Fourier resolution is about ±10 m, whereas Paracou forest height ranges from 20 m to 40 m. Thanks to these features, image formation along the vertical direction has been carried out through a coherent focusing, without resorting to super-resolution techniques nor to model based approaches.…”
Section: Tropical Paracou Data-setsmentioning
confidence: 99%
“…The aim of the study reported in this paper is to demonstrate the use of tomographic information to retrieve tropical forest biomass based on the experimental results from the Pband data acquired by ONERA in Paracou, French Guayana, in the frame of the ESA campaign TropiSAR 2009 [8].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation method is based on data from the airborne campaign TropiSAR 2009 [9] and the ground-based campaign TropiScat [10], [11], both carried out in the tropical forest site of Paracou, French Guiana, as part of BIOMASS Phase-A activities. Data from TropiSAR 2009 were used to generate a high-resolution 3-D reconstruction of the scattering elements within the Paracou forest, which was used as the basis for the retrieval of tropical forest biomass in [4] and [2] and for physical analysis in [12], [13].…”
Section: Introductionmentioning
confidence: 99%